2014
DOI: 10.1111/jopr.12139
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength and Nanoleakage of Weakened Roots Reconstructed Using Relined Glass Fiber–Reinforced Dowels Combined with a Novel Prefabricated Core System

Abstract: The fracture resistance of wide root canals can be improved by using glass fiber-reinforced dowels relined with composite resin as an alternative to increasing the thickness of luting cement; however, the percentage nanoleakage would increase. On the other hand, the recently introduced prefabricated glass fiber-reinforced core can be considered a promising technique, but further investigations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“… and Amin et al . ). The techniques of customization of glass fibre posts with composite resin, adopted in this and other studies, may explain the similar results, because the protocols employed were able to match the values of fracture resistance of intact and weakened roots.…”
Section: Discussionmentioning
confidence: 97%
“… and Amin et al . ). The techniques of customization of glass fibre posts with composite resin, adopted in this and other studies, may explain the similar results, because the protocols employed were able to match the values of fracture resistance of intact and weakened roots.…”
Section: Discussionmentioning
confidence: 97%
“…(23) Study was reported that thicker root dentin walls significantly increase the fracture resistance of endodontically treated teeth. (24) Endocrown preparation preserves root tissue and limits internal preparation of the pulp chamber to its anatomic shape depending on the high bonding capacity of lithium disilicate ceramics to the dental structure. (20) Higher fracture strength values of endocrowns group may also be attributed to the thickness of the ceramic occlusal portion of endocrowns.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to not being esthetically satisfactory, this type of intraradicular retainer requires greater clinic time to fabricate it and wear and tear on the already fragile crown structure [5]. Another important factor is that, due to the metal's high elastic modulus when compared to that of root dentin, the core transfers a large part of the masticatory forces received directly to the root, which may result in fractures [6, 7]. …”
Section: Introductionmentioning
confidence: 99%